2017
DOI: 10.1007/s11356-017-9148-5
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and respiratory health among diabetic and non-diabetic subjects in Pune, India—results from the Wellcome Trust Genetic Study

Abstract: Diabetics may be more vulnerable to the harmful effects of ambient air pollutants than healthy individuals. But, the risk factors that lead to susceptibility to air pollution in diabetics have not yet been identified. We examined the effect of exposure to ambient PM on chronic symptoms and the pulmonary function tests (PFT) in diabetic and non-diabetic subjects. Also, to investigate possible determinants of susceptibility, we recruited 400 type 2 diabetic and 465 healthy subjects who were investigated for chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Based on the background literature review, roundtable discussions, and a participatory workshop documented in the issue brief, the conceptual model is premised on several factors: Air pollution poses a significant public health risk [ 50 ]; this risk is under-recognized by the public; air pollution is inadequately monitored and managed [ 65 ]; and documenting air quality through an AQI and communicating specific exposure mitigation strategies can improve public health and facilitate long-term improvement of air quality [ 25 , 51 , 66 ]. Another underlying premise is that certain populations are at greater risk to air pollution-related health effects because of relatively high exposures (e.g., occupational exposures among outdoor workers, including traffic police, construction workers, and street vendors, among others [ 42 , 67 , 68 ]) or low coping capacity (e.g., school children, patients with pre-existing respiratory illnesses [ 69 , 70 , 71 ]). The model also posits that strategies for conveying risk information and corresponding exposure mitigation recommendations would reduce the population health risks related to air pollution [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the background literature review, roundtable discussions, and a participatory workshop documented in the issue brief, the conceptual model is premised on several factors: Air pollution poses a significant public health risk [ 50 ]; this risk is under-recognized by the public; air pollution is inadequately monitored and managed [ 65 ]; and documenting air quality through an AQI and communicating specific exposure mitigation strategies can improve public health and facilitate long-term improvement of air quality [ 25 , 51 , 66 ]. Another underlying premise is that certain populations are at greater risk to air pollution-related health effects because of relatively high exposures (e.g., occupational exposures among outdoor workers, including traffic police, construction workers, and street vendors, among others [ 42 , 67 , 68 ]) or low coping capacity (e.g., school children, patients with pre-existing respiratory illnesses [ 69 , 70 , 71 ]). The model also posits that strategies for conveying risk information and corresponding exposure mitigation recommendations would reduce the population health risks related to air pollution [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…The peer-reviewed public health literature was surveyed to better understand the burden of air pollution in Ahmedabad, as well as the need for improved air quality monitoring data at higher spatial and temporal resolution. The focus was on the quantification of health effects in vulnerable sub-populations in the city, including children [ 69 , 84 ], the elderly [ 85 ], people with pre-existing medical conditions [ 70 , 86 , 87 , 88 ] and those exposed to especially high levels of pollution due to their socioeconomic status [ 89 , 90 ] or occupation [ 67 , 68 , 91 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies revealed that particulate matter collected from different locations all over the world is strongly associated with the elevated morbidity and mortality and various diseases [8-13]. Several studies have attempted to understand the link between PM isolated from heavily populated regions of India and associated health concerns in term of occurrence of disease [14-19]. Although, most of the studies were based on the epidemiological data and cross-sectional studies, there were few studies about involvement of PM in respiratory diseases [20-22], asthma [23], cancer [24-27], tuberculosis [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…If the exposure to such volatile compounds is eternal it can result in health issues like respiratory problems, damage to central nervous system and are carcinogenic [1]; [20]; [25]. Mortality in patients having long term exposure to such odorous gases can be caused by obnoxious reactions like stress on physical as well as mental health which involve respiratory problems, anxiety headache, vomiting, irritation in eye and other health problems [3]; [14]; [16]; [17]; [18]; [28]; [36];. These issues have led to rising concerns and complaints for analysis of odour pollution [23]; [36]; [38].…”
Section: Introductionmentioning
confidence: 99%